Tingkat Kesukaan Konsumen Terhadap Teh Gaharu (Aquilaria malaccensis Lamk.) Berdasarkan Bentuk dan Ukuran serta Kandungan Antioksidan - Jhonny Simatupang; Ridwanti Batubara; Elisa Julianti (Program studi Kehutanan USU, 2015)
Agarwood (Aquilaria malaccensis Lamk.) are now popular to be exploited by farmers as a healthy drink. This research was done to study the effect of the shape and size of the tea from agarwood leaves on the consumers acceptance and antioxidant content. Agarwood leaves tea made in three forms: whole leave, cutted and fine particle size. Agarwood tea from these three size of shape and size then were evaluated of their hedonic level at 0 day and after 2 months of storaged in room temperatur by 50 panelists. The antioxidant activity was evaluated on methanol extracts from the three kinds ofagarwood leaves tea by using DPPH method after 2 month of storage. The result of the research shows that the froporcle of agarwood leave tea was more liked by panelists followed by the cutted leaves tea and the whole leaves tea had the lowest value of the hedonic score. The same result was found on the agarwood leaves tea that had been storage for 2 months, in the term of aroma, color for aswell as taste. The hedonic score of arom, color and taste of agarwood leaves tea after 2 months of storage till more than 3,00. It showed that the agarwood leaves tea still was accepted by panelists. The result of antioxidant activity evaluation showed that the fine particle size of agarwood leaves tea had the highest antioxidant activity. The value of IC50 of the agarwood leaves tea from the whole, cutted an fine size leaves were 85,89; 150,01; and 73,02 ppm respectively. Keywords: Agarwood leaves, organoleptic, antioxidant activity, tea